PENENTUAN GROSS TONAGE KAPAL PURSE SEINE DENGAN PENDEKATAN PEMODELAN FISIK DI TEGAL, JAWA TENGAH: PENENTUAN GROSS TONNAGE KAPAL PURSE SEINE DENGAN PENDEKATAN PEMODELAN FISIK DI TEGAL, JAWA TENGAH - Suharyanto Suharyanto; Ratih Purnama Sari; R. Mohamad Adha Akbar; Yaser Krisnafi; Tonny Kusumo (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2025)
The research was carried out at the dock and shipping companies, PT. Indonesian Fisheries, PT. Tiara, and village cooperative unit (KUD) Karya Mina, at Tegal, Central Java, in October 2023. The research aims to determine the percentage change in shape of the ship’s hull below deck, Cb (coefficient block) and GT (gross tonnage) values of purse seiners in the Tegal using a physical model that is dipped in water. The Cb and GT values research was focused on KM. Himalaya SB with 84.44% accuracy. The results at the three dock and shipping companies showed that the change in the shape of the ship’s hull below deck, on average, in part I, II, III, IV, and V were 14%, 20%, 30%, 11%, and 25%, respectively, and in the case of KM. Himalaya SB part I, II, III, IV, and V were 15%, 18%, 29%, 9%, and 29%, respectively. The shape was dominated by shapes III and V. The ones that increase Cb and GT values were shape III with a U shape. The results of the average percentage change in shape for 6 ships, including the case example purse seiner, have a pattern that tends to be the same. The Cb value obtained from the experimental results was 0.82 > 0.70 from the